2020
DOI: 10.1021/acsnano.0c06375
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mRNA Expression Using Single-Molecule Nanopore Sensing

Abstract: RNA quantification methods are broadly used in life science research and in clinical diagnostics. Currently, real-time reverse transcription polymerase chain reaction (RT-qPCR) is the most common analytical tool for RNA quantification. However, in cases of rare transcripts or inhibiting contaminants in the sample, an extensive amplification could bias the copy number estimation, leading to quantification errors and false diagnosis. Single-molecule techniques may bypass amplification but commonly rely on fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 53 publications
(80 reference statements)
0
60
0
Order By: Relevance
“…Nanopore translocation is a powerful single-molecule probing technique that has been used in diverse contexts: from studying the physical response of homopolymers [19-21, 32, 34, 39], to the topological friction in chains with knots and links [33,[40][41][42][43][44][45][46][47][48], for sequencing and analyzing biopolymers' secondary and tertiary structures [7,11,29,41,[49][50][51][52][53][54][55][56][57], and study RNA too [1][2][3][4][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Nanopore translocation is a powerful single-molecule probing technique that has been used in diverse contexts: from studying the physical response of homopolymers [19-21, 32, 34, 39], to the topological friction in chains with knots and links [33,[40][41][42][43][44][45][46][47][48], for sequencing and analyzing biopolymers' secondary and tertiary structures [7,11,29,41,[49][50][51][52][53][54][55][56][57], and study RNA too [1][2][3][4][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Pore translation has recently allowed for distinguishing different types of tRNAs 1 and quantifying mRNA expression. 2 Measurements of ionic current blockades in nanopores 3 have been used to sequence RNAs 4 to probe salient features of their folding pathway 5 and to detect modified nucleobases. 6 Molecular dynamics simulations have shown that driving RNAs through pores of appropriate width can relay information about their compliance to structural deformations 7 and directional mechanical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Given the breakdown voltage depends approximately linearly on the membrane thickness, 143 this will result in nanopores forming at the thinnest part of the membrane. This technique has been demonstrated using a He + FIB 164 and EBL followed by RIE 12,158 to locally thin regions of the membrane. However, the large capital cost of these instruments limits the availability of this method for many researchers.…”
Section: Advanced Controlled Breakdown Methodsmentioning
confidence: 99%
“…being developed for commercial applications such as DNA sequencing, [6][7][8] protein analysis, 9,10 and analyte detection in ultra-dilute samples. [11][12][13] As such, single-molecule biosensing devices hold promise for future applications such as early stage diagnostics and personalised medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation